Melayu Social Siasat on The Rakit House Community in Palembang - Ibrahim, Mohammad Syawaludin (DINIKA : Academic Journal of Islamic Studies, 2018)
This study aims to illustrates the social relations carried out by the entity of the Rakit House in Palembang. The social relations happened in this society is considered as forms of seeking survival and ways of maintaining life from changes in economic, cultural and power systems. Such relations are also known for social tactics. The main question of this study is what are the patterns of Malay social relations living in the Palembang Rakit House community. With phenomenological qualitative and sociological theory of figuration and configuration approach, this studi find that the social functions in the entity of the Palembang rakit house are organic functions that are directly felt by the local community such as; social solidarity between residents and communities. the life of the Palembang rakit house entity is one form of locality civilization that is able to live and survive in the social system.